Weblog as an Appropriate Online Medium in Teaching Writing - Sandi Pradana; Ashadi Ashadi (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
This research aims to develop weblog as media in teaching writing of senior high school students.It is a research and development (R&D) study that follows ASSURE model proposed by Heinrich and developed by Smaldino, Heinich, Molenda, & Russell (2005:49). The procedure of developing media consisted of analyzing learner, stating objective, selecting media, utilizing media, requiring learner participation, evaluating and revising.The product was examined by the media expert. After conducting the first test, the second test was conducted by English teacher and students. The subjects of this research were the eleventh grade students of PGN 1 High school. The subject consisted of 19 students of class XI. The researcher used an interview and questionnaires as the data collecting technique. The questionnaires were distributed for needs analysis and expert validation. English teacher and studentsâ€™ responded toward the developed weblog. The data were analyzed using descriptive statistics for the questionnaires and the qualitative analysis technique for the interview.The findings revealed that the developed weblog as online media in teaching writing is categorized â€œvery goodâ€ by experts with the mean scores put on 3.82. The result score of tryout is 3.48 and categorized as very good. The English teacherâ€™s response towards the weblog show the range of average mean score on 3.69 categorized â€œvery goodâ€. Therefore, the developed weblog is very appropriate to use in teaching and learning process of writing.